Status, population fluctuations and ecological relationships of Peary caribou on the Queen Elizabeth Islands: Implications for their survival - Miller, Frank L.; Gunn, Anne (Rangifer, 2003)
The Peary caribou (Rangifer tarandus pearyi) was recognized as ’Threatened’ by the Committee on the Status of Endangered Wildlife in Canada in 1979 and ’Endangered’ in 1991. It is the only member of the deer family (Cervidae) found on the Queen Elizabeth Islands (QEI) of the Canadian High Arctic. The Peary caribou is a significant part of the region’s biodiversity and a socially important and economically valuable part of Arctic Canada’s natural heritage. Recent microsatellite DNA findings indicate that Peary caribou on the QEI are distinct from caribou on the other Arctic Islands beyond the QEI, including Banks Island. This fact must be kept in mind if any translocation of caribou to the QEI is proposed. The subspecies is too gross a level at which to recognize the considerable diversity that exists between Peary caribou on the QEI and divergent caribou on other Canadian Arctic Islands. The Committee on the Status of Endangered Wildlife in Canada should take this considerable diversity among these caribou at below the subspecies classification to mind when assigning conservation divisions (units) to caribou on the Canadian Arctic Islands. In summer 1961, the first and only nearly range-wide aerial survey of Peary caribou yielded a population estimate on the QEI of 25 845, including about 20% calves. There was a strong preference for range on the western QEI (WEQI), where 94% (24 363) of the estimated caribou occurred on only 24% (ca. 97 000 km2) of the collective island-landmass. By summer 1973, the overall number of Peary caribou on the QEI had decreased markedly and was estimated at about 7000 animals. The following winter and spring (1973-74), the Peary caribou population declined 49% on the WQEI. The estimated number dropping to <3000, with no calves seen by us in summer 1974. Based on estimates from several aerial surveys conducted on the WQEI from 1985 to 1987, the number of Peary caribou on the QEI as a whole was judged to be 3300-3600 or only about 13-14% of the 1961 estimate. After a partial recovery in the late 1980s and early 1990s, Peary caribou on the WQEI declined drastically between 1994 and 1997 and were estimated at an all-time known low of about 1100 animals by summer 1997. The number of Peary caribou on the QEI in summer 1997 was likely no more than 2000-2400 or only 8-9% of the 1961 estimate. The four known major die-offs of Peary caribou on the WQEI between 1973 and 1997 occurred during winter and spring periods (1 Sep-21 Jun) with significantly greater (P<0.005) total snowfall, when compared to the long-term mean obtained from 55 caribou-years (1 Jul-30 Jun), 1947/48-2001/02, of weather records from Resolute Airport on Cornwallis Island. Of ecological significance is that the die-offs occurred when the caribou were at low mean overall densities and involved similar high annual rates of loss among muskoxen (Ovibos moschatus). All of the available evidence indicates that Peary caribou (and muskoxen) on the QEI experienced die-offs from prolonged, under-nutrition (starvation) caused by relative unavailability of forage-the forage was there but it was inaccessible to the caribou due to snow and/or ice cover. We cannot control the severe weather that greatly restricts the forage supply but we should try to reduce the losses of Peary caribou from other sources-humans, predators and competitors.